First application of the GPU-based software framework TIGRE for proton CT image reconstruction. (April 2021) - Kaser, Stefanie; Bergauer, Thomas; Birkfellner, Wolfgang; Burker, Alexander; Georg, Dietmar; Hatamikia, Sepideh; Hirtl, Albert; Irmler, Christian; Pitters, Florian; Ulrich-Pur, Felix
Highlights: First application of the GPU-based framework TIGRE to proton CT image reconstruction. Geant4 simulations were used to generate reconstruction input data. A straight-line approximation allowed reconstruction within seconds. Tomographic images of two Catphan modules were analyzed. An image resolution of three line pairs per cm was achieved. Abstract: In proton therapy, the knowledge of the proton stopping power, i.e. the energy deposition per unit length within human tissue, is essential for accurate treatment planning. One suitable method to directly measure the stopping power is proton computed tomography (pCT). Due to the proton interaction mechanisms in matter, pCT image reconstruction faces some challenges: the unique path of each proton has to be considered separately in the reconstruction process adding complexity to the reconstruction problem. This study shows that the GPU-based open-source software toolkit TIGRE, which was initially intended for X-ray CT reconstruction, can be applied to the pCT image reconstruction problem using a straight line approach for the proton path. This simplified approach allows for reconstructions within seconds. To validate the applicability of TIGRE to pCT, several Monte Carlo simulations modeling a pCT setup with two Catphan® modules as phantoms were performed. Ordered-Subset Simultaneous Algebraic Reconstruction Technique (OS-SART) and Adaptive-Steepest-Descent Projection Onto Convex Sets (ASD-POCS) were used for image reconstruction. Since the accuracy of the approach is limited by the straight line approximation of the proton path, requirements for further improvement of TIGRE for pCT are addressed.